Second international symposium on silica, silicosis and cancer - Goldsmith, D. F.; Wagner, G. R.; Saffiotti, U.; Rabovsky, J.; Leigh J (guest, ). (Scandinavian Journal of Work, Environment & Health, 1995)
The Second International Symposium on Silica, Silicosis, and Cancer, held 27 30 October 1993 in San Francisco, California, was convened to address research and risk assessment issues surrounding the toxicity and carcinogenicity of crystalline silica. The Second Symposium followed the First by 10 years and was designed to highlight the progress made in the past decade. In so doing, the papers in this special issue of the Scandinavian Journal of Work, Environment & Health from the 1993 Symposium have accomplished the following two major objectives: 1) expanded knowledge about silica from the fields of medical toxicology, industrial hygiene, epidemiology, and tumor biology and 2) described new areas of research in physicochemistry, biological mechanisms, mineralogy, risk assessment, and prevention. The contents of this issue are the result of the submission of 56 manuscripts from the 102 presentations from the San Francisco Symposium. Included in this group are two papers requested by the Editors from Amandus and his co-workers and Partanen and his colleagues to summarize occupational epidemiology studies conducted in North Carolina and Finland. All the manuscripts were peer-reviewed by at least two scientists using a standard review format and were rated for acceptability. These reviews were transmitted to the Editor-in-Chief of the special issue and, when there was disagreement, a third opinion was sought. Through this process, the editors accepted 28 papers for publication and added a last summary paper. The accepted papers have been organized into the following five sections: 1) Physicochemistry, Tumor Biology and Cellular Mechanisms, 2) Silica Sampling, Industrial Hygiene and Modeling, 3) Epidemiology of Silica, Silicosis, and Cancer, 4) Environmental and Workplace Risk Assessments, and 5) Future Research Directions and Areas of Focus. Section 1 consists of seven papers describing the physical and chemical properties of silica dusts and their differential ability to produce fibrogenesis and carcinogenesis. Section 2 includes several interesting papers on methods for collecting quartz samples and applying silica dust levels. Of note are the contributions describing dust levels in Chinese industries, North Carolina soils, and the application of physiological models to estimate dust levels in the respiratory system. Section 3 extends the literature linking industrial silica exposure to silicosis and the roles silica exposure and the presence of silicosis play in cancer risks. Some highlights include silicosis surveillance in Ontario, Canada, the follow-up of Chinese silica brick workers, health risks among Italian silicotics and ceramic workers, and lung cancer findings from Michigan and New Jersey silicotics. Section 4 is a new contribution to this field a description of risk assessment research focusing on silica-related health risks among workers and people potentially exposed from ambient sources. The research in this section derives from previous work in epidemiology, toxicology, pulmonary medicine, industrial hygiene, and biostatistics. Section 5 provides a guide for future research in this field, with particular attention drawn to biogenic amorphous silica and compensation issues. The editors of the special issue conclude by summarizing the growth in silica, silicosis, and cancer knowledge over the past 10 years, suggesting fruitful areas for new endeavors.